Perencanaan persediaan bahan baku amoxicillin menggunakan metode material requirement planning: studi kasus - Firda Pratiwi; Sawarni Hasibuan (Universitas Mercu Buana, 2020)
PT. XYZ is a pharmaceutical company that produces Amoxicillin. In managing its inventory, PT XYZ has not done a good plan to determine the size of raw material orders. The existence of these problems, a study was conducted with the aim of determining Amoxicillin raw material inventory planning to eliminate the accumulation of raw materials at future. The initial stage is forecasting using three methods, namely Linear Regression, Exponential Smoothing and Moving Average. Of the three forecasting methods, the Linear Regression method provides the smallest error accuracy. The chosen method of forecasting must be carried out in advance of verification test (Moving Range) to be used as a basis for planning future raw material requirements. Furthermore, calculations are carried out using the MRP method to determine the size of the order lot for each raw material and reduce the cost of saving. The lot size technique used includes Lot for Lot (LFL), Economic Order Quantity (EOQ), and Fixed Period Requirement (FPR). Of the three lot size techniques used, the LFL method provides the lowest total cost of inventory.